Pengaruh NPM, DER terhadap ROE pada Perusahaan Properti dan Real Estate yang terdaftar di BEI (2021-2024) - Djalalludin Akbar; Mutiara Hayandani; Anggun Fitria Novianti; Fadila Siti Nuraeni; Alfiana Alfiana (Indo Publishing, 2026)
This study aims to examine the impact of net profit margin (NPM) and debt-to-equity ratio (DER) on return on equity (ROE) in property companies listed on the Indonesia Stock Exchange (IDX). Previous studies have shown that although NPM has a significant positive effect on ROE, the effect of DER depends on the company's leverage level. Simultaneously, it has been proven that both NPM and DER have a significant effect on ROE. As a result, policies that encourage profit efficiency and a balanced capital structure are likely to be crucial factors in increasing equity profits for companies in the property sector. However, the researchers' findings state that DER has no effect on ROE, while NPM affects ROE in property and real estate companies listed on the Indonesia Stock Exchange.